Uveal Melanoma Mimicking Advanced Coats' Disease in a Young Patient - Gupta, Naina (Ocul Oncol Pathol, 2016)
BACKGROUND/AIMS: To report a case and the unique histopathology of a necrotic uveal melanoma mimicking advanced Coats’ disease in a young adult. METHOD: A 26-year-old male presented with a blind, painful eye, total exudative retinal detachment, and bulbous aneurysms consistent with Coats’ disease. No masses were visualized on ultrasound or CT scan, and the patient underwent enucleation of the eye. RESULTS: Histopathology of the involved eye confirmed a necrotic uveal melanoma with persistent spindle cells forming a collar around residual tumor vessels. CONCLUSION: Careful consideration is needed in approaching any patient with a blind, painful eye and opaque media, even in younger populations.